The science of sport sprinting - Platt, Geoffrey K. Dr. (The Crowood Press Ltd. Ramsbury, Marlborough Wiltshire, 2015)
The Science of Sports: Sprinting examines the scientific principles that underpin the preparation and performance of athletes at all levels, from grassroots to Olympic competition. Drawing on the expertise of some of the world's leading coaches and sport science professionals, this book presents a detailed analysis of the latest evidence and explores the ways in which science has influenced, and subsequently improved, the sport of sprinting. The Science of Sport series is essential reading for students and academics, coaches and performers, physiotherapists, club doctors and professional support staff working in the sport. key topics covered include: Talent identification and youth development; Biomechanics; Performance analysis; Coaching and coach education; Training methods; Fitness testing; Nutrition; Mental skills; Incidence and treatment of injuries; Performance lifestyle.
1. An introduction to the science of sprinting/ Dr. Geoffrey K. Platt -- 2. Talent identification and development in sprinting/ Dr. Mohsen Shafizadeh -- 3. Biomechanical analysis of the techniques of the sprint start/ Professor Morteza Shabazi Moghaddam -- 5. Biomechanics of sundry sprint skills/ Professor Morteza Shabazi Moghaddam -- 6. Performance analysis in sprinting/ Dr. Mohsen Shafizadeh -- 7. Coaching sprinting/ interview with Tom McNab -- 8. Training methods 1960-2014/ Dr. Geoffrey K. Platt -- 9. Modern training methods/ Dr. Geoffrey K. Platt -- 10. Fitness testing for sprinting/ Dr. Geoffrey K. Platt -- 11. Nutrition for sprinting/ Dr. Justin Roberts -- 12. Drugs in sprinting/ Wilf Paish, Tom McNab and Dr. Geoffrey K. Platt -- 13. Mental skills training in sprinting/ Dr. Andrew Cruickshank Susan Giblin and Professor Dave Collins -- 14. Incidence and treatment of injuries in sprinting/ Dr. Geoffrey K. Platt -- 16. References
Cover design by Maggie Mellet
Front and back cover photos by Getty Images
Includes bibliographies and index
Keywords: Sprinting; Sprinting -- Training